STRATEGI PEMASARAN APARTEMEN SETIABUDI SKYGARDEN JAKARTA - Cicih Ratnasih; Bambang Irawan (Fakultas Ekonomi Universitas Borobudur, 2020)
This study aims to examine and analyze the influence of factors related to the purchasedecision of Setiabudi Skygarden Apartment Jakarta. These factors include Product Quality andPromotion, which subsequently functioned as independent variables that influence purchasedecisions that function as dependent variables, while purchase interest is a variable that isdiffused as an intervening variable. The research method used in this study is path analysis.The results showed that there is a direct effect of product quality and promotion onpurchase interest and purchase decisions both simultaneously and partially. The purchaseinterest as an intervening variable is able to mediate the indirect influence of product qualityand promotion on purchase decisions, with the results of a suitability test of a decent model.Keywords: product quality, promotion, purchase interest, purchase decision